PS1:6 Differential diagnosis of autoimmune diseases, outlier detection plus subgrouping in clinical trials by high content autoantibody profiling. (21st March 2018) - Schulz-Knappe, P; Budde, P; Zucht, H-D
Abstract : Purpose: Early diagnosis as well as initiation of successful treatment are two big challenges in the management of patients with autoimmune diseases (AID). Overlap of a plethora of clinical symptoms, ranging from multi-organ involvement, fatique, inflammation to CNS-involvement make differential diagnosis quite challenging. Especially in early disease these signs are difficult to quantify, hence the lag time from start of disease until clinical diagnosis may be delayed, sometimes for years. With the growing interest in conducting clinical trials in AID, there is a need for new biomarkers that can be used to diagnose individual AIDs to reduce the inclusion of patients not carrying the intended disease, and identify clinical subsets, predict treatment outcome and assess disease activity. Methods: The autoantibody reactivity pattern in serum of AID patients was analysed using a Luminex bead-based antigen array (SeroTag) and 1, 600–8000 selected human protein antigens. We screened over 3000 serum samples from Sjögren's Syndrome (n=350), SLE (n≥1000), SSc (n≥250), RA (n≥1000), and several other AIDs and over 1000 healthy individuals to confirm known and to discover novel autoantibodies, create reduced autoantibody panels for differential diagnosis and disease subgrouping. Results: Apart from clear confirmation of the known benchmark autoantigens known for many years we have discovered over 80 novel autoantibodies, which were detected in frequencies of 10 to >25% in selected AIDs. Some novel autoantibodies are specific for certain diseases, such as the major vault protein in SLE or BICD2 in SSc. Others are present in several diseases, indicating overlap syndromes. Multiplex panels of 50–100 AABs were generated and tested to allow for a subgroup definition of Sjögren's, SLE, and for clear segregation of SjS/SLE overlap syndrome patients. As well, subgrouping of SSc and early RA patients was achieved. Conclusions: A set of 100–150 autoantigens, half of them well established, the other half novel, succeed in differential diagnosis of AID, in some diseases already at early disease stage. This panel has been used in several drug trials to subgroup SLE, Sjögrens or RA into subgroups. Especially in SLE, outliers in the range of 10%–15% of the trial population were seen which can be used to curate a trial population, eventually to arrive at a more precise assessment of trials primary objectives.